Intergating multiple metrics to improve the performance of a routing protocol over wireless mesh networks - Rahman, Md. Arafatur; Azad, Md. Saiful; Anwar, Farhat (2009)
Wireless Mesh Networks (WMNs) are dynamically self-organized and self-configured, with the nodes in the network automatically establishing an ad hoc network and preserving the mesh connectivity. There are several features which might help to design an efficient routing protocol suitable for wireless mesh networks such as improved performance metrics, link or path optimization, mobility management, scalability, cross-layer design etc. Since WMNs are permanent or semi-permanent network, an efficient and reliable path establishment is the core concern for such type of networks. By using the improved performance metrics, a reliable path can be established between source and destination. Minimum hop-count is the metric most commonly used by existing routing protocols. This approach implicitly assumes that links either work well or don't work at all. While often true in wired networks, this is not a reasonable approximation in the wireless case; since many wireless links have intermediate loss ratios, interference problem, low throughput etc. For this reason, several performance metrics are already designed for WMNs such as Expected Transmission Count (ETX), Expected Transmission Time (ETT), Interference Aware Routing Metric (iAWARE), Link Type Aware (LTA) Metric, Success Probability Product (SPP) and so on. However, each individual routing metric consider some features and it is difficult to satisfy all the requirements of WMNs by using a single metric. Consequently, it is necessary to integrate multiple performance metrics into a routing protocol to attain optimal performance. This paper proposes a technique of integrating multiple routing metrics to improve the performance of a routing protocol. This technique is implemented in Ad hoc On-Demand Distance Vector (AODV) routing protocol and corresponding performance has been investigated in wireless mesh environment. Simulation results demonstrate significant performance improvement over standard AODV in WMNs.